North Carolina Women : Their Lives and Times - McMillen, Sally G. (Sally Gregory), 1944-; Gillespie, Michele (Book collections on Project MUSE., 2014)
North Carolina has had more than its share of accomplished, influential women-women who have expanded their sphere of influence or broken through barriers that had long defined and circumscribed their lives, women such as Elizabeth Maxwell Steele, the widow and tavern owner who supported the American Revolution; Harriet Jacobs, runaway slave, abolitionist, and author of Incidents in the Life of a Slave Girl ; and Edith Vanderbilt and Katharine Smith Reynolds, elite women who promoted women's equality. This collection of essays examines the lives and times of pathbreaking North Carolina women f.